War for Work’s Sake - Maria Bose (Media Theory)
This essay evaluates the ideological compact between U.S. state violence deployed across a decades-long War on Terror and that violence’s foremost cultural mediator, the post-9/11 Hollywood war film. It argues that, counter the tendency to view the Hollywood war film as mere “ideological apparatus,” a media form conscripted into the project of U.S. imperialism, what implicates state and medium is instead a more immanent strategy of mutual self-justification and institutional renewal powered by nostalgia for the Fordist-industrial mode of production and its gendered division of labor. Less neoliberal-imperial jingo than neo-protectionist, post-imperial swansong, the post-9/11 Hollywood war film diagnoses rather than refutes U.S. declension, tracing that declension, as economists Robert Brenner and Giovanni Arrighi do, to the 1970s crises in industrial “overcapacity” and “over accumulation” that precipitated U.S. deindustrialization. The genre moreover implicates Hollywood’s own declension in that systemic diagnosis, coarticulating the institution’s struggle to adapt to increasingly fragmented production processes. The genre’s insistently retrograde protagonists embody a fantasy of reindustrialization in the shadow of global outsourcing, widespread deskilling, and imminent automation that ultimately sublimates war’s violence into the labor of artistic production, binding Hollywood’s fortunes and failures to the state while staking the state’s renewal on Hollywood’s. Doing so, they subsequently convey the cinematic medium’s structural implication in US state violence while affirming its primacy to US hegemony’s maintenance.